Determination of antibodies to Flavivirus in wild birds from Buenos Aires City - Krapp, Federico (2022)
Saint Louis encephalitis virus (SLEV), West Nile virus (WNV) and Ilheus virus (ILHV) are flaviviruses maintained in nature by enzootic transmission networks between mosquitoes and birds. These viruses have been detected in South America and identified as a cause of neurological diseases in humans. There is a record of activity in monkeys and birds for ILHV in Chaco, Corrientes and Misiones; of WNV in horses and birds in the center and east of the country, while SLEV is widely distributed in Argentina and there is virological and serological evidence in birds, humans and various mammals. In order to detect viral circulation in free-living birds in the Autonomous City of Buenos Aires (CABA), seasonal sampling was carried out in the Costanera Sur Ecological Reserve.